1994
DOI: 10.1159/000187772
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Metabolism in Aminonucleoside-Induced Nephrotic Syndrome

Abstract: Copper (Cu) and zinc (Zn) were measured in urine, serum and tissues from rats with nephrotic syndrome (NS) induced with a single subcutaneous dose of puromycin aminonucleoside (PAN; 15 mg/l00 g BW). Control animals were pair-fed. Urine was collected daily, and the rats were sacrificed on day 10. PAN-nephrotic rats had proteinuria (days 3-10), high urinary Cu (days 1,2,4-10) and Zn (days 3-10) excretion. On day 10, nephrotic rats had: (a) albuminuria, hypoalbuminemia, hypoproteinemia, high urine and low serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Additionally, we found that plasma zinc level was lower in the NS group in active and remission phase, which is in good agreement with the results published by Reimold [16] and Perrone et al [7], but not with those of Mishra et al [9], who observed no difference between NS and control groups in terms of plasma zinc level. Furthermore, in an experimental study, low serum v and high urinary zinc excretion were observed in nephrotic rats [17]. There are studies reporting an impaired oxidant-antioxidant balance in children with NS [8,9,18].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, we found that plasma zinc level was lower in the NS group in active and remission phase, which is in good agreement with the results published by Reimold [16] and Perrone et al [7], but not with those of Mishra et al [9], who observed no difference between NS and control groups in terms of plasma zinc level. Furthermore, in an experimental study, low serum v and high urinary zinc excretion were observed in nephrotic rats [17]. There are studies reporting an impaired oxidant-antioxidant balance in children with NS [8,9,18].…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that urinary copper excretion is significantly correlated with urinary protein excretion in aminonucleoside-induced nephrotic rats (15) and patients with NS (16)(17)(18). However, except for one case of severe proteinuria (33 g/L) due to congenital NS (19), no cases of severe copper and Cp depletion causing severe anemia have been previously reported in the setting of human NS, as the rate of copper excretion via urinary nephrotic excretion [1.0 to 4.0 μmol (15,16)] is less than that of physiological absorption via the small intestine [0.5 to 1.5 mg (7.9 to 23.6 μmol) per day (4)].…”
Section: Discussionmentioning
confidence: 99%
“…However, except for one case of severe proteinuria (33 g/L) due to congenital NS (19), no cases of severe copper and Cp depletion causing severe anemia have been previously reported in the setting of human NS, as the rate of copper excretion via urinary nephrotic excretion [1.0 to 4.0 μmol (15,16)] is less than that of physiological absorption via the small intestine [0.5 to 1.5 mg (7.9 to 23.6 μmol) per day (4)]. It is likely that, in our patient, the copper deficiency-associated bicytopenia was caused primarily by the lack of copper in the long-term TPN therapy and not by the excretion of copper via urinary nephrotic excretion.…”
Section: Discussionmentioning
confidence: 99%
“…While the urinary loss of this 151 kDa protein may cause a decrease in blood copper [6,8], it results in no clinically recognized manifestations [176]. The most important zinc-binding protein is albumin, with the greatest losses occurring in the nephrotic syndrome.…”
Section: Derangements In Divalent Cation Metabolism In the Nephrotic mentioning
confidence: 99%